Frequency reconfigurable circular microstrip patch antenna with slots for cognitive radio - Mohamed Labiod; Zoubir Mahdjoub; Mohamed Debab (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
In this paper, a novel multi-frequency microstrip antenna with complementary ring slot resonator (CRSR) structure that satisfies Bluetooth, worldwide interoperability for microwave access (WiMAX), and wireless local area network (WLAN) applications is proposed. The conventional antenna consists of a circular microstrip patch at a resonance frequency band of 2.5 GHz. By loading two CRSR at the radiating element, three operating frequency bands 2.5 GHz, 3.6 GHz, and 5.2 GHz are achieved. The operational bands covered by the antenna are Bluetooth 2.5 GHz, WiMAX 3.6 GHz, and WLAN 5.2 GHz. The insertion of CRSR to patch antenna has made it possible to compact and simple design, and miniaturized antenna for cognitive radio. Moreover, the directivity of the proposed antenna is adequate with acceptable radiation properties and perfectly matches with the simulated and measured results.